2017
DOI: 10.1038/s41598-017-00392-5
|View full text |Cite
|
Sign up to set email alerts
|

Posterior cingulate cross-hemispheric functional connectivity predicts the level of consciousness in traumatic brain injury

Abstract: Previous studies have demonstrated that altered states of consciousness are related to changes in resting state activity in the default-mode network (DMN). Anatomically, the DMN can be divided into anterior and posterior regions. The anterior DMN includes the perigenual anterior cingulate cortex and other medial prefrontal cortical regions, whereas the posterior DMN includes regions such as the posterior cingulate cortex (PCC) and the temporal parietal junction (TPJ). Although differential roles have been attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
11
1
1
Order By: Relevance
“…This result suggests that PACC's scale-free resting state properties are specifically related to a differentiation of animate from inanimate stimuli in task-evoked activity. Analogous findings of specific relations between scale-free properties and mental features have been observed regarding the self (Huang et al 2016) and consciousness (Zhang et al 2017). This is well in line with our finding of animate task evoked activity being specifically predicted by resting state PLE (rather than ALFF, ReHo, and SD).…”
Section: Resting State Activity-brain's Spontaneous Activity Predictssupporting
confidence: 90%
See 1 more Smart Citation
“…This result suggests that PACC's scale-free resting state properties are specifically related to a differentiation of animate from inanimate stimuli in task-evoked activity. Analogous findings of specific relations between scale-free properties and mental features have been observed regarding the self (Huang et al 2016) and consciousness (Zhang et al 2017). This is well in line with our finding of animate task evoked activity being specifically predicted by resting state PLE (rather than ALFF, ReHo, and SD).…”
Section: Resting State Activity-brain's Spontaneous Activity Predictssupporting
confidence: 90%
“…Recent functional magnetic resonance imaging (fMRI) studies demonstrated that the degree of LRTCs predisposes the neural processing of motor (Palva et al 2013) and sensory stimuli (Huang et al 2015;He 2011) as well as private self-consciousness (Huang et al 2016). Together, these studies suggest that spontaneous activity's scale-free properties may shape task-evoked activity and associated behavioral features including consciousness (Northoff and Huang 2017;Zhang et al 2017). The exact neural mechanisms of such rest-stimulus interaction including the relevant neuronal features (He 2013;Huang et al 2015;Northoff et al 2010) as well as the exact kind of external stimuli that are preferentially mediated by the spontaneous activity's scale-free properties remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to share a phenomenological basis with the difficulty in localizing the self in space associated with a PCC lesion. Furthermore, in the resting brain, the PCC is functionally connected to the TPJ (Mars et al , ); the PCC and TPJ both lie in the posterior region of the default‐mode network (one of the central resting brain networks; Zhang et al , ). Anatomically, the PCC projects to the macaque homologue of the inferior parietal lobule and the superior temporal sulcus, both of which are TPJ regions (Parvizi, Van Hoesen, Buckwalter, & Damasio, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, current evidence highlights the role of the posteromedial cortex (PMC) in regulating the consciousness levels in humans as a central hub between the networks (Crone et al, 2015 ; Silva et al, 2015 ; Zhang et al, 2017 ). The PMC, including the PCC and precuneus, is one of the most metabolically active brain regions.…”
Section: Brain Metabolism and Loss Of Consciousnessmentioning
confidence: 99%